Evaluation of serum alpha-1B glycoprotein and C-reactive protein levels as biomarkers of canine benign prostatic hyperplasia - Grisnarong Wongbandue; Sekkarin Ploypetch; Piyada Pruksakitcharoen; Kittithee Udomrit; Kanisa Nujan; Rinrada Seekhumtae; Tanapron Thubthim; Nawarus Prapaiwan (Veterinary World)
Background and Aim: Benign prostatic hyperplasia (BPH) is a prevalent disorder in aging male dogs, characterized by prostate enlargement secondary to hormonal dysregulation and chronic inflammation. Identifying non-invasive biomarkers is crucial for improving diagnosis and monitoring therapeutic interventions. This study aimed to evaluate serum alpha-1B glycoprotein (A1BG) and C-reactive protein (CRP) concentrations in dogs with BPH before and after castration, to assess their diagnostic and prognostic utility.